Securitization and crash risk: Evidence from large European banks - Francesca Battaglia; Bonnie G. Buchanan; Franco Fiordelisi; Ornella Ricci (Bank of Finland, 2018)
The 2008 global financial crisis highlights the importance of securitization and crash risk. Yet there is a dearth of papers exploring the link between securitization and crash risk. We analyze 7,096 securitization deals made by large European listed banks between 2000 and 2017. Our paper provides evidence that bank risk declines in the year of the securitization and increases in the following year. We also show that this effect is driven by low-risk securitization deals. We use a dynamic panel data approach to establish a causal relationship and control the robustness of our results by using different tail risk measures (such as crash risk, value at risk, and expected shortfall). We also show that the risk reduction effect is weaker in crisis periods relative to normal times. Our findings have policy implications as regulators attempt to revive European securitization markets.
URN:NBN:fi:bof-201812112153
Keywords: F30; G01; G14; G21; G32; 330